1976
DOI: 10.1070/rm1976v031n05abeh004194
|View full text |Cite
|
Sign up to set email alerts
|

Absolutes of Topological Spaces and Their Continuous Maps

Abstract: Dissolution studies were carried out on NaCl crystals, some pure and some doped with various impurities. It was observed that etch pits associated with beaks are obtained only in NaCl crystals doped with CaC12, if the etchant reported by Hari Babu and Bansigir is used. Of the 26 poisons studied with methyl alcohol as base, only a few of the cadmium and lead salts are capable of giving beaks in NaCI:CaCh, whereas with the other poisons etch pits without beaks are obtained. These investigations reveal that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In [24] the first author has shown that in the category Top of topological spaces with continuous maps, every space X admits a cover p : P → X with respect to the full subcategory Ed of extremally disconnected spaces, and that p coincides with the absolute [23,25,27] of X. To distinguish p from the object P , we will also call P the absolute, and refer to p as the absolute cover of X.…”
Section: Corollarymentioning
confidence: 98%
See 1 more Smart Citation
“…In [24] the first author has shown that in the category Top of topological spaces with continuous maps, every space X admits a cover p : P → X with respect to the full subcategory Ed of extremally disconnected spaces, and that p coincides with the absolute [23,25,27] of X. To distinguish p from the object P , we will also call P the absolute, and refer to p as the absolute cover of X.…”
Section: Corollarymentioning
confidence: 98%
“…In [24], the first author proves that every topological space X admits a cover p : P → X with respect to the full subcategory of extremally disconnected spaces, and that p coincides with the absolute [23,25,27] of X (see Section 5). Furthermore, he characterizes the strongly projectable hull in terms of spectra.…”
mentioning
confidence: 99%
“…We define an absolute (cf. [31,35,38]) of X to be an essentially dense perfect map p : P → X such that P is extremally disconnected. Let Ed ⊂ Top denote the full subcategory of extremally disconnected spaces.…”
Section: The Absolutementioning
confidence: 99%
“…Apart from being perfect, an absolute p has to be surjective and "irreducible", where the latter concept has found several interpretations or replacements [3,4,29,31]. Our approach is categorical: Since perfect maps are closed, it makes no difference if "surjective" is replaced by dense, i.e.…”
mentioning
confidence: 99%
“…The construction of the absolute has been extended to successively larger classes of spaces by Gleason [12], Strauss [38], and the Russian school [31]. Some of the deepest results on extremally disconnected spaces can be found in Efimov [8].…”
Section: Has the Strong Lifting Property (Slp) If For Each μEmi(x)mentioning
confidence: 99%